Diseño y construcción de un prototipo de sistema germicida automatizado de radiación UV-C (2022)
This paper presents the design and administration of UVconstruction of an automatic prototype for the C radiation by implementing Phytopathogen control techniques. This device uses radiation cycles (exposure time and latency) and control strategies to manage variables such as the radiation distance, in which the plant material will be exposed in a programmed manner by means of a lamp connected to a power system, according to the requirements given by the company Flexport de Colombia SAS. The prototype allows radiation administration tests t o be carried out on samples of flower crops, as an experimental basis for later development of an application model in the post harvest phase.The development of this technology allows equipment for the control of pathogens to a target market composed main ly of the agricultural, food and flower sectors. To achieve this longterm objective, it is necessary, in this initial phase, to build a first prototype that allows preliminary laboratory and field tests to be carried out. For this, the company Flexport de Colombia S.A.S. has been supported, who have proposed and supported the development of this research by the UAN.